Enhanced Denitrification Bioreactors Hold Promise for Mid‐Atlantic Ditch Drainage. Issue 1 (1st December 2017) - Christianson, L. E.; Collick, A. S.; Bryant, R. B.; Rosen, T.; Bock, E. M.; Allen, A. L.; Kleinman, P. J. A.; May, E. B.; Buda, A. R.; Robinson, J.; Folmar, G. J.; Easton, Z. M.
Abstract : Core Ideas: Bioreactors can be designed to remove nitrate from drainage ditches. Designing bioreactors for ditch drainage requires site‐specific flexibility. All mid‐Atlantic ditch bioreactors tested removed nitrate from drainage water. Practical concerns will require adjustments to design and installation. There is strong interest in adapting denitrifying bioreactors to mid‐Atlantic drainage systems to help address Chesapeake Bay water quality goals. Three ditch drainage‐oriented bioreactors were constructed in 2015 in Maryland to evaluate site‐specific design and installation concerns and nitrate (NO3 –N) removal. All three bioreactor types removed NO3 –N, as measured by load and/or concentration reduction, showing promise for denitrifying bioreactors in the mid‐Atlantic's low gradient Coastal Plain landscape. The ditch diversion bioreactor (25% NO3 –N load reduction; 0.97 g NO3 –N removed m −3 d −1 ) and the sawdust denitrification wall adjacent to a ditch (>90% NO3 –N concentration reduction; 1.9–2.9 g NO3 –N removed m −3 d −1 ) had removal rates within range of the literature. The in‐ditch bioreactor averaged 65% NO3 –N concentration reduction, but sedimentation is expected to be one of the biggest challenges. A robust water balance is critical for future assessment of bioreactors' contribution to water quality improvement in low gradient mid‐Atlantic landscapes.